2011
DOI: 10.1111/j.1445-6664.2011.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from the subterranean part of Johnsongrass and their allelopathic potential

Abstract: The allelopathic effects of the exotic invasive weed, Johnsongrass, on Lactuca sativa, a native plant in China, were evaluated and the phytotoxins were investigated under laboratory conditions.The crude extracts (chloroform and ethyl acetate fractions) that were obtained from the ethanol extract of the subterranean parts of Johnsongrass inhibited the germination speed and growth of the roots and shoots of the test plant. The four compounds, ethyl p-hydroxybenzoate, diosmetin, apigenin, and luteolin, were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…; Liu et al . ). The phenolic compounds, p ‐hydroxybenzoic acid ( p ‐HBA) and p ‐hydroxybenzaldehyde ( p ‐HBAL), were identified as the dominant allelochemicals that are present in the leaf and rhizome extracts (Nicollier et al .…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…; Liu et al . ). The phenolic compounds, p ‐hydroxybenzoic acid ( p ‐HBA) and p ‐hydroxybenzaldehyde ( p ‐HBAL), were identified as the dominant allelochemicals that are present in the leaf and rhizome extracts (Nicollier et al .…”
mentioning
confidence: 97%
“…; Liu et al . ). The previous research showed that these two phytotoxins could inhibit the germination or seedling growth of several other plant species (Abdul‐Wahab & Rice ; Liu et al .…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Due to the specificity of producing metabolites that are exudated directly in the environment, many compounds with relevant biological activities have been located almost exclusively in roots (OLIVEROS-BASTIDAS et al, 2009). Extracts and allelopathic phytotoxins obtained from roots have been reported to interfere in several plant development processes, including germination (SANTOS et al, 2007), root and shoot growth, normal seedling rate (LIU et al, 2011;GRISI et al, 2013), metaxylem cell growth (GATTI et al, 2010), photosynthesis, respiration and membrane transport (DAYAN et al, 2009) literature, suggesting a need for further investigation of the phytotoxic properties of roots. The results obtained for extracts of the different D. brasiliensis plant parts were compared using a joint analysis.…”
Section: ♦ Radish ('Y)mentioning
confidence: 99%